PENERAPAN WEBGIS DALAM MENDUKUNG AKSESIBILITAS INFORMASI PASAR TRADISIONAL DI WILAYAH LAMPUNG TENGAH - Ricco Herdiyan Saputra; Dita Novitasari; Winia Waziana (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2026)
Traditional markets in Central Lampung Regency play a vital role in supporting the local economy; however, the lack of spatial information and limited data accessibility remain major challenges in their management and utilization. This study aims to design and implement a WebGIS system to map traditional markets interactively, provide detailed market information, and support route navigation. The research employed a software engineering approach using the Waterfall model, which includes requirements analysis, system design, implementation, testing, and deployment. Data were collected through field surveys using GPS and supported by secondary documentation sources. The results indicate that the WebGIS application successfully displays an interactive market map, presents detailed information such as address, district, description, and photo documentation, and offers route navigation features. Both blackbox and whitebox testing confirmed that the system’s main functions run properly and meet user requirements. Therefore, the developed WebGIS effectively enhances accessibility to traditional market information while supporting local governments in data-driven decision-making.